Healthcare students' awareness of Universal Design for Learning (UDL) in anatomy curricula: An Irish single institution-based study - Audrey M.K. Dempsey; Eithne Hunt; Yvonne M. Nolan; Mutahira Lone (Elsevier, 2024)
Healthcare students perceive anatomy as a difficult subject to study, yet there is limited literature to explain why students think that anatomy is difficult to learn. Studies have assessed student opinion of anatomy teaching strategies, but there is no specific research regarding healthcare students' perception of pedagogical frameworks utilised in anatomy curricula. Considering the importance of student experience, the design of anatomy curricula should include the perspectives of students. Universal Design for Learning (UDL) is a framework which aims to optimise learning opportunities. There is no specific research on healthcare students' awareness or perception of UDL in anatomy curricula. A questionnaire was administered to first-year undergraduate medical, dental, occupational therapy (OT) and speech and language therapy (SLT) students studying anatomy. Demographic data and participants' perception of UDL were gathered. The response rate was 83%. The majority of participants were female (69%) and studied medicine (59%). Ninety-seven percent of participants had not heard of UDL. After a brief explanation of UDL, 91% thought that UDL had been implemented in anatomy laboratory sessions and 52% thought UDL had been implemented in anatomy lectures. Although the majority of participants were not aware of UDL, they identified aspects of UDL in their anatomy curriculum. UDL helps create an inclusive learning experience. The discussion about the design and delivery of anatomy curricula should include the opinions and perspectives of healthcare students.